ALGORITHMIC SCHEMAS FOR COMPUTER-AIDED DESIGN OF FOUNDRY TECHNOLOGIES - A. N. Chichko; T. V. Matjushinets; V. F. Sobolev; L. V. Markov (Литьë и металлургия, 2008)
The algorithmic schemas allowing to increase the degree of automation of design efforts aimed at development and improvement of the castings production technology are offered. The offered schemas are described for one of industrial castings.